Variasi Waktu pada Posisi Berbaring Saat Pungsi Vena terhadap Kadar Kolesterol Total - Muhammad Dandy Pratama; Hanifullah Hafidz Arrizal; Nafiatul Ilmi (Jaringan Laboratorium Medis, 2020)
Laboratory internal quality assurance includes pre-analytic, analytic and post-analytic stages. The error in the pre-analytic reached 68%, 25% in the analytic stage, while in the post-analytic stage it was approximately 14%. The aim of this study to determine the effect of supine position treatment during venous puncture to the total cholesterol level of respondents at minutes 0 ', 10', 20 'and 30'. The method used is a quasi-experimental method. Research subject are 6 STr TLM semester 3 and 5 students using the method sampling by non random sampling. There is a change of -3.2% in the 10th and 20th minutes, there is also a change of -1.6% in the 10th and -30th minutes. Statistical analysis is presented using the one-way ANOVA test, it is said that there are significant differences if the p value <0.05. Result: there was no significant difference on levels total cholesterol (p = 0.068) of respondents who were treated while lying down a venous puncture is performed. Conclusion: there is no significant difference in levels cholesterol of respondents who were treated lying down for 30 minutes at a time a venous puncture is performed.